KEKUATAN PERMINTAAN DAN PENAWARAN SUBSEKTOR TANAMAN BAHAN MAKANAN DALAM PEREKONOMIAN WILAYAH PROPINSI SULAWESI TENGAH - Marwan R. Yantu; Sisfahyuni Sisfahyuni; Ludin Ludin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The aim of the study was to analyze the power of demand and supply of  food crop subsector in regional economy of Central Sulawesi Province. Method of analyses used were the modified shift and share analysis. Data used were time series data, such as Gross Domestic Regional Product of Central Sulawesi, and Gross Domestic Product of Indonesia, during 2000 – 2008. The analyses results showed that power of supply side of the food crops subsector was signed possitively, and very significant, so the subsector growth was pushed up fully (100%) by its supply side. Consequently, the subsector is the prime mover of agriculture sector in regional economy of Central Sulawesi Provincial.